Atrioventricular Block in a Patient Followed Up with a Diagnosis of Epilepsy - Morkavuk, Gulin; Koc, Guray; Gokoglan, Yalcin; Kabul, Hasan Kutsi; Leventoglu, Alev; Gokcil, Zeki (Turkish Neurological Soc, 2018)
[Abstract Not Available]
Keywords: Video electroencephalographic monitoring; seizure; atrioventricular block